Lutein and Astaxanthin Supplementation Induce Competitive Inhibition of Carotenoid Deposition in Egg Yolk - Xia Chen; Zhixun Yan; Bing Zhang; Lingchao Zeng; Urmita Chowdhury; Mohammad Hasanuzzaman Pabitra; Jing Cao; Zhipeng Wang; Yanghua He; Huagui Liu; Qin Chu (Animals, 2025)
Lutein- and astaxanthin-fortified eggs can greatly improve both nutritional and economic values of eggs. High doses of lutein and astaxanthin are often supplemented in hen diets to rapidly accumulate lutein and astaxanthin in eggs. In this study, an additional 100, 200, and 400 mg/kg lutein and astaxanthin were added in hen diets to explore the effects of high-dose lutein and astaxanthin on egg quality, egg production, and carotenoid deposition in eggs, which remains unclear. The results showed that high-dose lutein and astaxanthin supplementation had no significant impact on laying rates and egg quality, except for markedly improving yolk color. Additionally, a quantitative profile of carotenoids in egg yolk was performed through liquid chromatography–mass spectrometry. A total of 26 carotenoids were detected including 14 whose concentrations exceed 0.1 µg/g. Notably, the zeaxanthin content in yolk decreased with the increase in levels of lutein supplementation. Conversely, the content of lutein, zeaxanthin, 5,6 epoxy-lutein-caprate-palmitate in yolk decreased as astaxanthin supplementation increased. These findings suggest that high doses of lutein and astaxanthin supplementation may competitively inhibit the deposition of other carotenoids in egg yolk. Overall, this study suggests that during the production of functional eggs enriched with lutein and astaxanthin, it is important to consider the interaction effects among different carotenoids.